Proceeding of International Conference on Intelligent Communication, Control and Devices ICICCD 2016 - Singh, Rajesh; Choudhury, Sushabhan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book presents high-quality research papers presented at the first international conference, ICICCD 2016, organised by the Department of Electronics, Instrumentation and Control Engineering of University of Petroleum and Energy Studies, Dehradun on 2nd and 3rd April, 2016. The book is broadly divided into three sections: Intelligent Communication, Intelligent Control and Intelligent Devices. The areas covered under these sections are wireless communication and radio technologies, optical communication, communication hardware evolution, machine-to-machine communication networks, routing techniques, network analytics, network applications and services, satellite and space communications, technologies for e-communication, wireless Ad-Hoc and sensor networks, communications and information security, signal processing for communications, communication software, microwave informatics, robotics and automation, optimization techniques and algorithms, intelligent transport, mechatronics system, guidance and navigation, algorithms, linear/non-linear control, home automation, sensors, smart cities, control systems, high performance computing, cognition control, adaptive control, distributed control, prediction models, hybrid control system, control applications, power system, manufacturing, agriculture cyber physical system, network control system, genetic control based, wearable devices, nano devices, MEMS, bio-inspired computing, embedded and real-time software, VLSI and embedded systems, FPGA, digital system and logic design, image and video processing, machine vision, medical imaging, and reconfigurable computing systems.
Automatic Segmentation of Brain MRI of Newborn & Premature Infants Using Neural Network -- Chapter 90. An Efficient Handoff Using RFID Tags -- Chapter 91. A Robust and Fast Technique to Detect Copy Move Forgery in Digital Images Using SLIC Segmentation and SURF Keypoints -- Chapter 92. VPBC: A Varying Probability Based Clustering for Energy Enhancement in WSN -- Chapter 93. Biosignal Acquisition of Stress Monitoring through Wearable Device -- Chapter 94. Implementation of Heartbeat Sensing Using PSoC3 -- Chapter 95. Design and Implementation of Wearable Device for Water Management System for Household Usage -- Chapter 96. High Speed-Low Power Divide-By-16/17 Dual Modulus Prescaler Using C2MOS -- Chapter 97. Design and Optimization of Luggage Tracking System on Airport -- Chapter 98. Contact Thickness Variation Effect on Performance of Novel Organic Thin Film Transistor -- Chapter 99. Comparative Analysis of Various Adaptive Filter Structures Using Simulink -- Chapter 100. Experimental Investigations on the Effects of Dust Fouling on PV Module -- Chapter 101. Study of Parametric Effects on Solid Oxide Fuel Cell -- Chapter 102. Performance Investigation of ANN Controller Assisted Small Hydro Power Generation System -- Chapter 103. GA Tuned 2DOFPID Based Biomass Concentration Control of Bioreactor -- Chapter 104. Microcontroller and FPGA Based Analysis of 8 x 48 LED Matrix Display with Keyboard Interface -- Chapter 105. Software Reliability Prediction Based on Ensemble Models -- Chapter 1.
Keywords: Computational intelligence; Telecommunication; Control engineering; Signal processing; Computational Intelligence; Communications Engineering, Networks; Control and Systems Theory; Signal, Speech and Image Processing